Molecular delimitation of the seasonal killifishes of the Hypsolebias antenori species group (Cyprinodontiformes, Rivulidae), with description of two new species from the Caatinga coastal basins, northeastern Brazil - Abrantes, Yuri Gomes; Ramos, Telton Pedro Anselmo; Bento, Diego De Medeiros; Lima, Sergio Maia Queiroz (Zootaxa, 2023)
Hypsolebia antenori is a seasonal killifish considered to be broadly distributed along the Caatinga’s basins of northeastern Brazil, with records in the coastal drainages of the rio Pacoti, rio Jaguaribe, córrego Virgílio and rio Apodi-Mossoró basins. Based on morphological characters and molecular phylogenetic reconstructions, it was possible to diagnose two new species and restrict H. antenori to the rio Jaguaribe basin. Hypsolebias gongobira new species is described from a temporary pool in the rio Pacoti basin in Ceará State, in syntopy with the species threatened H. longignatus. Hypsolebias bonita new species occurs in the floodplains of the rio Apodi-Mossoró basin and in the córrego Virgílio microbasin in the Furna Feia National Park, in Rio Grande do Norte State. We also discuss the conservation status of these new species and how the São Francisco Interbasin Water transfer, and the agricultural and urban expansion in the semiarid may be adversely affecting these seasonal killifishes.